1997
DOI: 10.1038/ng0397-311
|View full text |Cite
|
Sign up to set email alerts
|

A non-epistatic interaction of agouti and extension in the fox, Vulpes vulpes

Abstract: Agouti and extension are two genes that control the production of yellow-red (phaeomelanin) and brown-black (eumelanin) pigments in the mammalian coat. Extension encodes the melanocyte-stimulating hormone receptor (MC1R) while agouti encodes a peptide antagonist of the receptor. In the mouse, extension is epistatic to agouti, hence dominant mutants of the MC1R encoding constitutively active receptors are not inhibited by the agouti antagonist, and animals with dominant alleles of both loci remain darkly pigmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
131
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(135 citation statements)
references
References 19 publications
4
131
0
Order By: Relevance
“…By contrast, dominant gain-of-function mutations of the MC1R resulted in black hair due to increased eumelanin biosynthesis. Subsequently, a similar pattern of action has been reported in a variety of other animals with loss-offunction leading to yellow or red hair and dominant mutations leading to black pigment (16,(23)(24)(25)(26)(27)(28)(29)). Cone's paper (22) is worth re-reading, 8 years on, for the insights it provided about the MC1R and human pigmentation; that the MC1R would lead to red hair in man; that mutant alleles of the MC1R would be common; and that the gene would be of interest to those interested in human evolution.…”
Section: The Cloning Of the Melanocortin 1 Receptorsupporting
confidence: 60%
“…By contrast, dominant gain-of-function mutations of the MC1R resulted in black hair due to increased eumelanin biosynthesis. Subsequently, a similar pattern of action has been reported in a variety of other animals with loss-offunction leading to yellow or red hair and dominant mutations leading to black pigment (16,(23)(24)(25)(26)(27)(28)(29)). Cone's paper (22) is worth re-reading, 8 years on, for the insights it provided about the MC1R and human pigmentation; that the MC1R would lead to red hair in man; that mutant alleles of the MC1R would be common; and that the gene would be of interest to those interested in human evolution.…”
Section: The Cloning Of the Melanocortin 1 Receptorsupporting
confidence: 60%
“…Sequence comparison for MC1R regions that span amino acid 5 (amino acid 1-9 in the left box) and 280 (region 276-284, or 274-282 in mouse which has a two aa deletion). For the regions illustrated, additional species have been shown to be identical to species included in this figure [5,[10][11][12]16,18,25,26]. rable to the TM2/TM3 -mutations might be foreseen.…”
Section: Resultsmentioning
confidence: 99%
“…Inter-species crossing between the winter white arctic fox and the standard silver variant (aaE + E + ) of the red fox (Vulpes vulpes) provide firm evidence for a functional agouti protein in the arctic fox. The standard silver fox do not carry a functional agouti protein, and the red color found in the offspring (named Golden island) must therefore be ascribed the functional "arctic" agouti protein [17,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been cloned (Mountjoy et al, 1992) and mapped to human chromosome 16q24.3 (Gantz et al, 1994;Magenis et al, 1994). In mammals the orthologue of the MC1R gene, the extension locus (e), was found mutated in those with red and yellow coat colours (Robbins et al, 1993;Vage et al, 1997). Studies on the molecular basis of the red hair and pale skin phenotype in humans have shown that the MC1R gene plays a role in this pigmentation type (Valverde et al, 1995;Box et al, 1997;Koppula et al, 1997;Smith et al, 1998;Rana et al, 1999).…”
Section: Introductionmentioning
confidence: 99%